Effect of OPT (Plant Pest Organism) Mechanical Control Method on Sugar Yield and Quality of Sugarcane Stalks (Saccharum Officinarum L.) - Ajeng Syadiar Junaedi (Jurnal Indonesia Sosial Teknologi, 2026)
This literature study examines the effect of mechanical control of Plant Disrupting Organisms (OPT) on sugarcane cultivation (Saccharum officinarum L.), particularly its impact on sugar yield and stem quality. The mechanical control methods discussed include manual weeding, klenthek (cutting old leaves), pruning/roaming of pest-infested areas, and the use of traps (pheromones, lamps, nets). The results of the study showed that weed weeding greatly improved the light penetration and photosynthesis efficiency of sugarcane plants (as heavy weeds such as Ipomoea triloba can cover the crown up to 100% and inhibit photosynthesis. Periodic weeding results in better stem growth – greater stem height and diameter – compared to without weeding. The klenthek technique accelerates the hardening of the bark of the stem and stimulates the growth of sugarcane stalks so that the plant is sturdier. Mechanical control of pests such as stem borers (with roges and pheromone traps) and larval retrieval in the field prevent physical damage to the plant, so that photosynthesis, sucrose accumulation, and the strength of sugarcane stalks remain optimal. Finally, mechanical control of OPT has been shown to be positively correlated with an increase in sugar yield and Pol/Brix levels: for example uncontrolled weeds can reduce stem production by up to 25% and reduce yield significantly, while every 1% of segment damage due to stem borer pests can reduce sugarcane yields by 0.5%. Therefore, mechanical management of OPT is essential to improve crop yields and sugarcane quality. The report summarizes findings from various national scientific journals, reports of agricultural institutions, and related technical guidelines.